Pattern of the Spread of Archaeological and Touristic Sites in The City of Nablus and Easily Accessible Analysis Using Geographic Information Systems - ABAHRE, Jafar Subhi Hardan; BURQAN, Mohammad (Journal of Environmental Management and Tourism; Vol 10 No 8 (2019): JEMT Volume X Issue 8(40) Winter 2019DO - 10.14505//jemt.v10.8(40).20, 2020)
The study showed a mechanism to apply methodology to access the spatial distribution of archaeological and tourist landmarks in the city of Nablus, through spatial analysis tools available within an environment, which have the capacity to analyze metadata in order to identify the spatial characteristics through a study of the spatial geographic phenomena, in order to identify the spread of the distribution of the archaeological and tourists sites in the city. The study adopted a descriptive approach analytical work in data processing, and hired some statistical methods, and cartography within an environment of Geographic Information System (GIS); for the most prominent archaeological spatial characteristics of the feature. The study showed that there is a clear disparity in the geographical distribution of archaeological and tourist sites; they distributed the touristic and monumental differently on the city, the results of the spatial analysis showed that the pattern of geographical distribution of archaeological sites, tourism is the distribution of the thin pattern (the distances are not regular), heads to random distribution pattern of spatial analysis showed that the direction of the geographical spread of the places studied, the prevalence of most of the archaeological sites throughout the city, especially the actual average takes into account the actual locations of each archaeological centers, and could be access to all the sites of during the course of the 52.6 km in length and the time it takes to follow this path on a vehicle speed of 30 km/hour is 1:45, and the vehicle speed is 40 km/hour is 1:19, and the speed of the vehicle 50 m/h is 1:03, and the speed of a vehicle 60 km/hour is 53 minutes.